2016
DOI: 10.5812/jjm.30257
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem Susceptibility and Multidrug-Resistance in Pseudomonas aeruginosa Isolates in Egypt

Abstract: BackgroundResistant Pseudomonas aeruginosa is a serious concern for antimicrobial therapy, as the common isolates exhibit variable grades of resistance, involving beta-lactamase enzymes, beside native defense mechanisms.ObjectivesThe present study was designed to determine the occurrence of Metallo-β- Lactamases (MBL) and Amp C harboring P. aeruginosa isolates from Suez Canal university hospital in Ismailia, Egypt.MethodsA total of 147 P. aeruginosa isolates, recovered from 311 patients during a 10-month perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This was demonstrated in the present study as more than 50% of isolates were MDR. A nearby percent of MDR P. aeruginosa (43.8%) was reported by El-Domany et al [35] and a higher percent (64%) by Hashem et al [36]. Our isolates were associated with high resistance rate to piperacillin, cefoperazone/sulbactam, gentamicin and quinolones (48.7% -61.5%).…”
Section: Discussionsupporting
confidence: 52%
“…This was demonstrated in the present study as more than 50% of isolates were MDR. A nearby percent of MDR P. aeruginosa (43.8%) was reported by El-Domany et al [35] and a higher percent (64%) by Hashem et al [36]. Our isolates were associated with high resistance rate to piperacillin, cefoperazone/sulbactam, gentamicin and quinolones (48.7% -61.5%).…”
Section: Discussionsupporting
confidence: 52%
“…( b ) Previous reports for AMR found in Pseudomonas isolated from different sources in Egyptian clinical settings. Data are taken from a range of the literature [84, 86, 110–128, 129]. ESBL, extended-spectrum β-lactamase; MBL, metallo-β-lactamase.…”
Section: Resultsmentioning
confidence: 99%
“…The MBL positive isolates were distributed by gender, with 56.8% of the isolates being male and 43.2% female. Also, Hashem et al (13) found that the ratio of men to females was 1.8:1, with males making up 64.7% and females 35.3%. The study carried out by Sheikh et al (14) revealed very identical results, indicating that out of the 369 confirmed P. aeruginosa isolates, 219 (59.3%) isolates were acquired from male participants and 150 (40.7%) isolates from female cases.…”
Section: Discussionmentioning
confidence: 98%